UJI AKTIVITAS ANTIBAKTERI FRAKSI n-HEKSANA KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP PERTUMBUHAN Shigella flexneri SECARA IN VITRO - ., Umar Syarif Asifa (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: diarrhea is one of the health problems that still needs moreattention especially in developing countries such as Indonesia. Shigellaflexneri is a bacterial isolates were found in most cases of diarrhea. Basedon scientific information about Garcinia mangostana L., this plant has apotentcyÂ  as an alternative treatment of antibacterial. Objective: the aimedof this study was to determined the antibacterial activity of n-hexane fractionof mangosteen peels (Garcinia mangostana L.) and the effectiveconcentration to inhibit growth of Shigella flexneri Method: mangosteenpeels were extracted by maceration method using 90% methanol then thisextracts was fractionated using n-hexane. The chemical compound of nheksanefraction was screened by phytochemical screening. Antibacterialactivity was conducted by using well diffusion with concentration of 5%,10%, 20%, and 40%. Ciprofloxacin 5Î¼g/hole was used as positive controland DMSO 10% was used as negative control. Result: the phytochemicalscreening of n-heksana fraction of mangosteen peels is contains alkaloids,flavonoids, quinones and terpenoids. Concentration of 40% is the highestconcentration that has great antibacterial effect of all various concentrationtests but this concentration only moderate inhibition zone (p=0,000). Theinhibition zone of each concentration has decreased at 48 hours incubation.Conclusion: n-hexane fraction of mangosteen peels has antibacterialactivity against Shigella flexneri.. Â Keywords: Antibacterial, n-heksane fractions of mangosteen peels,Shigella flexneri1) Medical Education Study Program, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan2) Biology Study Program, Faculty of Mathematics and Natural Science, Tanjungpura University, Pontianak, West Kalimantan3) Department of Physiology, Medical Education Study Program, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan